Corotating twin‐screw extrusion of poly(lactic acid) PLA/poly(butylene succinate) PBS/ micro‐lamellar talc blends for extrusion blow molding of biobased bottles for alcoholic beverages - Aversa, Clizia; Barletta, Massimiliano; Gisario, Annamaria; Pizzi, Elisa; Prati, Rosa; Vesco, Silvia (Journal of applied polymer science, 2021)
Extrusion blow molding is a well‐established technology for the manufacture of fossil‐based plastic bottles. The process is, however, still little used for the manufacture of bottles with a low environmental footprint, especially those based on bioplastic from renewable sources. In this context, the objective of this work is precisely the study and experimental design of poly(lactic acid) PLA/poly(butylene succinate) PBS/micro‐lamellar talc compounds for the manufacturing of bioplastic bottles, basically for wine packaging. In particular, the design was carried out to ensure, primarily, an adequate processability of the bioplastic material in the blowing process. Second, the compound was loaded with different micro‐lamellar talc content so as to achieve protection from the environmental factors, which is of paramount importance to ensure a long shelf‐life to wine. The bio‐derived polyester resins are very complex to transform, as they are subject to thermo‐hydrolytic degradation phenomena during the processing of the polymer melt. Processability is further limited in the presence of high micro‐lamellar talc content that increases the melt viscosity, thus making the material even more difficult to shape by extrusion blow molding. The experimental analysis involved the use of a co‐rotating twin‐screw extruder for the manufacture of the bioplastic compounds. The compounds were first subjected to thermo‐rheological and physical characterization tests. Second, it was tested in the extrusion blow molding process. The experimental results have shown that blends based on bio‐derived polyester resins can be adequately processed by extrusion blow molding, showing extremely stable rheological behavior both during the extrusion phase of the parison and the subsequent blowing process of the parison itself. These blends have, therefore, an interesting potential to be used as an alternative with a low environmental footprint to oil‐based plastics in the production of wine bottles.